Laparoscopic radiofrequency ablation of functioning pancreatic insulinoma: video case report - Procházka, Vladimír; Hlavsa, Jan; Andrašina, Tomáš; Starý, Karel; Můčková, Katarina; Kala, Zdeněk; Válek, Vlastimil (Surgical laparoscopy, endoscopy & percutaneous techniques, 2012)
Insulinomas are the most common functioning endocrine tumors of the pancreas. Most of them are well-differentiated tumors, with benign or uncertain behavior at the time of diagnosis. Surgery is considered to be the only curative treatment modality. We present the first case report of a 75-year-old woman with functioning insulinoma of the pancreatic body, which was destroyed by laparoscopic-assisted radiofrequency ablation. Hypoglycemic paroxysms disappeared immediately after surgery. The postoperative course was uneventful. The patient was discharged on the eighth postoperative day. There was a new onset of diabetes mellitus, without any further hypoglycemic paroxysm from surgery to the present-4 months. Laparoscopic-assisted radiofrequency ablation is shown to be a feasible and safe method for the treatment of functioning pancreatic insulinoma.
Keywords: počítačová rentgenová tomografie; Pancreatectomy; pankreatektomie; diferenciální diagnóza; nádory slinivky břišní; Humans; laparoskopie; Female; Aged; Insulinoma; Diagnosis, Differential; senioři; lidé; katetrizační ablace; ženské pohlaví; Pancreatic Neoplasms; Tomography, X-Ray Computed; Laparoscopy; Catheter Ablation; inzulinom